An Experimental Study of the Uniaxial Failure Behaviour of Rock-Coal Composite Samples with Pre-existing Cracks in the Coal. (28th November 2019) - Chen, Shaojie; Ge, Yao; Yin, Dawei; Yang, Huisan
Abstract : Many hazards encountered during coal mining can be caused by the instability and failure of the composite structure of the coal seam and the surrounding rock strata. The defects present in the coal affect the structural stability of the composite structure. In this study, uniaxial compression tests were conducted on sandstone-coal composite samples with pre-existing cracks in the coal, combined with tests performed with an acoustic emission (AE) device and a digital video camera. The strength, macrofailure initiation (MFI), and failure characteristics of composite samples, as influenced by the coal's pre-existing cracks, were analysed. The coal's pre-existing cracks were shown to reduce the strength, promote the occurrence of MFI, and affect the failure characteristics of the samples. Vertical penetration cracks had much more pronounced effects on strength and MFI occurrence, especially vertical penetration cracks that penetrated through the centre of the coal. Horizontal penetration cracks had a much reduced effect on strength and MFI occurrence. The MFI caused a step shape in the stress-strain curve accompanied with a peak energy index signal and occurred around the original coal cracks. The MFI models predominantly exhibited crack initiation from the pre-existing coal cracks and surface spalling caused by crack propagation. The intact composite sample failure presented as an instantaneous failure, whereas the composite samples containing the pre-existing cracks showed a progressive failure. The failures of composite samples occurred predominantly within the coal and displayed an X-typed shear failure accompanied by a small splitting failure. Both the coal and sandstone were destroyed in the composite sample with vertical penetration cracks through the centre of the coal. Failure of the coal occurred through a splitting failure accompanied by a small X-typed shear failure, while the sandstone showed a splitting failure induced by crack propagation in the coal.